1996
DOI: 10.1021/bi952368s
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Studies of Microcystin-LR Using NMR Spectroscopy and Molecular Dynamics Calculations,

Abstract: NMR spectroscopy in aqueous and dimethyl sulfoxide/water solutions is used to determine the three-dimensional structures of microcystin-LR, a cyclic cyanobacterial heptapeptide toxin which is a potent inhibitor of type 1 and type 2A protein phosphatases. The conformations of this toxic peptide are studied using a simulated annealing (SA) protocol followed by refined SA calculations in vacuo and free MD simulations in water. Only one conformational family in each solvent is found. The peptide ring has a saddle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 36 publications
2
37
1
Order By: Relevance
“…The structure of microcystin-LY in dimethyl sulfoxide was described as being a boat-like ring with the Adda residue protruding form the concave side, which is more in line with our microcystin-LR and microcystin-LL structures. Recently, a paper was published comparing the structure of microcystin-LR in water and in dimethyl sulfoxide (30). In this study, microcystin-LR was found to have the same structure in water and dimethyl sulfoxide, and both structures were similar to our previously published free solution structure (1).…”
Section: Discussionsupporting
confidence: 77%
“…The structure of microcystin-LY in dimethyl sulfoxide was described as being a boat-like ring with the Adda residue protruding form the concave side, which is more in line with our microcystin-LR and microcystin-LL structures. Recently, a paper was published comparing the structure of microcystin-LR in water and in dimethyl sulfoxide (30). In this study, microcystin-LR was found to have the same structure in water and dimethyl sulfoxide, and both structures were similar to our previously published free solution structure (1).…”
Section: Discussionsupporting
confidence: 77%
“…In support of this assumption, it has been reported that MC derivatives, in which Adda is destroyed by ozonolysis, are not immunoreactive (Chu et al, 1989). Furthermore, three-dimensional NMRbased structure analysis of MCs (Trogen et al, 1996) and nodularin showed that Adda is the best-exposed part of both peptides. Adda will also be one of the best exposed parts of the MC molecule in conjugates produced both by conjugation through carboxy-groups or by conjugation through an introduced amino group.…”
Section: Discussionmentioning
confidence: 99%
“…MCs have the general structure cyclo-(D-Ala-L-X-erythro-b-methyl-D-isoAsp-L-Y-Adda-D-isoGlu-N-Methyldehydro-Ala), where Adda refers to the b-amino acid residue of 3-amino-9-methoxy-2,6,8-trimethyl-10-phenyl-deca-4,6-idenoic acid, and X and Y represent variable L-amino acids (Carmichael, 1992;Dawson, 1998). The unusual amino acid Adda is essential for expression of biological activity (Trogen et al, 1996). Until now, more than 60 structurally different microcystins have been identified (Carmichael, 1994;Dawson, 1998).…”
Section: Introductionmentioning
confidence: 99%